1996
DOI: 10.1111/j.1467-8624.1996.tb01717.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Political Violence on Palestinian Children's Behavior Problems: A Risk Accumulation Model

Abstract: Interviews with 150 Palestinian mothers and their children living amidst the Intifada in the West Bank were conducted to assess exposure to political violence and family negativity as risk factors associated with behavioral problems as measured by the Child Behavior Checklist. The number of risks present in the child's life was significantly correlated with the number of behavioral problems the child exhibited (R = .53, p < .001). The analysis further examined the role of gender, age, and community context in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
102
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 21 publications
7
102
1
2
Order By: Relevance
“…The few studies that have examined variables that seem to mediate or moderate the impact of violence have yielded findings consistent with those of research on other forms of traumatic stress. Variables such as the nature of the violent events to which children are exposed, the availability of familial and social supports during and following exposure to violence, the meaning that survivors of violence make of their experiences, and the range of coping strategies and resources available to victims of violence all seem to play roles in determining the long-term impact of violence on children's development [25,26,[29][30][31][32]. For children in war zones, gender and age are significant determinants of the type of violent and abusive experiences to which they are likely to be exposed.…”
Section: The Traumatic Impact Of Political Violencementioning
confidence: 97%
See 2 more Smart Citations
“…The few studies that have examined variables that seem to mediate or moderate the impact of violence have yielded findings consistent with those of research on other forms of traumatic stress. Variables such as the nature of the violent events to which children are exposed, the availability of familial and social supports during and following exposure to violence, the meaning that survivors of violence make of their experiences, and the range of coping strategies and resources available to victims of violence all seem to play roles in determining the long-term impact of violence on children's development [25,26,[29][30][31][32]. For children in war zones, gender and age are significant determinants of the type of violent and abusive experiences to which they are likely to be exposed.…”
Section: The Traumatic Impact Of Political Violencementioning
confidence: 97%
“…Critical factors seem to be the degree to which children were exposed to acts of violence before becoming displaced [23,24] and the degree to which children were supported during and after displacement [24][25][26]. A study of Palestinian children in the Gaza Strip, for example, found a positive relationship between the number of traumatic events children had experienced and the severity of the PTSD symptoms [27].…”
Section: The Traumatic Impact Of Political Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Of the few studies conducted thus far, most of them have investigated the first Intifada, between 1987 and 1993, and have focused mainly on the political and historical aspects of the Israeli-Palestinian conflict. In addition, some studies have been reported, highlighting the psychological consequences of the Intifada on Palestinian children and adolescents who have actively participated in the acts of protest and resistance (Baker, 1990;Barber, 2001;Garbarino & Kostelny, 1996;Khamis, 2000;Punamaki, Quata, & El Sarraj, 1997;Punamaki & Suleiman, 1990).…”
mentioning
confidence: 95%
“…In fact, most of the literature refers to studies carried out on populations whose schoolchildren are undergoing the ravaging effects of war and natural disasters, but does not suggest systematic or other operational interventions to resolve the problem (Dyregrov et al 2002;Garbarino and Kostelny 1996;Punamäki et al 2001;Quota and Odeh 2004;Thabet et al 2002;Thabet and Vostanis 2000). Although many non-governmental organizations (NGOs) and other bodies have developed guidelines and standards for how education should be administered in a crisis (INEE 2004;Morgan 2010;UNICEF 2005;Winthrop and Kirk 2006), they only refer in passing to the psychosocial problems involved in the creation of curricula.…”
Section: Introductionmentioning
confidence: 98%